Analisis Nilai Perusahaan pada Perusahaan Sub Sektor Makanan dan Minuman : Bukti Empiris di Bursa Efek Indonesia - Aulia Fahma Syaharani; Dhani Ichsanuddin Nur (Universitas Serang Raya, 2022)
The value of the company is the industry's ability which is reflected by the stock market price which is formed from the demand and supply in the capital market. This study aims to test and analyze the influence of the profitability variable on the value of the company and to determine the effect of the company size variable in moderating the relationship between profitability and the value of the company in the food and beverage sub-sector industry on the BEI. The basis for this research is the decline in the value of the company in the last 3 years due to a decrease in the income of middle-class consumers so that it has an impact on the weakening of purchasing power. Provisions for the sample in this study using purposive sampling method. Based on the qualifications in this study for the food and beverage sub-sector industry on the IDX for the 2017-2020 period, 17 companies were obtained that could be used as research samples. The analytical method used in this study uses the MRA (Moderated Regression Analysis) analysis technique. The results of this study show that profitability contributes to increasing firm value and firm size can strengthen the influence of profitability on firm value in food and beverage sub-sector companies. Keywords: Profitability; Firm Size; Firm Value.